Penaatan Perusahaan Tambang Batubara di Sawahlunto terhadap Peraturan Air Limbah Pertambangan - Indah Elok Mukhlisah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Muhlisah IE. 2020. Coal mining company compliance in sawahlunto to waste water regolutions of mining. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Coal is one of the important energy commodities in Indonesia, as with other mining activities in Indonesia, coal mining has also caused environmental damage is large enough in water, soil and forests. Monitoring of waste water in the coal mining area was conducted to determine the level of adherence to the industry quality standard mining waste water discharged into the environment. Monitoring carried out in two seasons (rainy and dry seasons) of eleven (11) coal mining companies (code A-K) which are in Sawahlunto, Indonesia. The wastewater of the coal mining industries. Measurements parameter done in the laboratory. The results of analysis compared with the Minister of Environment Decree No. 113 of 2003 on wastewater quality standard coal mining. By measurement the pH of water, the pH in range 3.33-7.86 in the rainy season and 2.71-7.98 in the dry season, therefore the pH value has exceeded the quality standard required by the Decree-LH No. 113 in 2003, the 6-9. Concentrations parameters of iron (Fe) in range 0.267-24.8 mg/L in the rainy season and 0.109-27 mg/L in the dry season, which exceeds the quality standards, 7 mg/L. Total Suspended Solid (TSS) still meets the quality standards at all locations, in the range 24-361 mg/L in the rainy season and 3.5-228 mg/L in the dry season. The concentration of manganese (Mn) in range 0.109-7.19 mg/L in the rainy season and 0.014-26.7 mg/L in the dry season, which exceeds the quality standards, 4 mg/L.